(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: After coronary artery disease and cancer, stroke is the third commonest cause of death in the developed countries. Mortality risk is quite variable among stroke patients. Careful and early risk evaluation of each patient is therefore important. Electrolyte imbalance is a common phenomenon after stroke, particularly in the elderly. This research will provide the information regarding electrolyte imbalance in stroke patients. Objective: To find out prevalence of different type of electrolyte imbalance between ischemic and hemorrhagic stroke patients. Method: This short term prospective observational study was done in Medicine dept. of MMCH. We valuated 50 patients of Stroke admitted in hospital. Venous blood sample was collected for electrolyte. Additional clinical data was recorded including detailed complications of Stroke. Results: Out of 50 patients of Stroke the percentage of hypernatremia, hyponatremia, hypokalemia, hyperchloremia, hypochloremia, metabolic acidosis and metabolic alkalosis were higher in patients with Hemorrhagic stroke (27.3%,18.2%, 9.1%,18.2%, 45.5%, 18.2% and 9.2% respectively) than ischemic stroke patients (3.6%,7.1%, 3.6%, 0%, 3.6%, 0%, and 2.6% respectively). TAJ 2016; 29(1): 39-42